Kinship, law and the unexpected : relatives are always a surprise - Strathern, Marilyn (Cambridge University Press, 2005)
"How can we hold in the same view both cultural or historical constructs and generalities about social existence? In response to this anthropological conundrum, Kinship, Law and the Unexpected takes up an issue at the heart of studies of society - the way we use relationships to uncover relationships. Relationality is a phenomenon at once contingent (on certain ways of knowing) and ubiquitous (to social life)."--BOOK JACKET.